"El consul de Rusea Antonov-Ovseenko en Barcelona dando la bienvenida de la tripulacion del barco Ruso". On his right: Toryho. Series of 5 photos. Copied from CNT collection
"El consul de Rusea Antonov-Ovseenko en Barcelona dando la bienvenida de la tripulacion del barco Ruso". On his right: Toryho. Series of 5 photos. Copied from CNT collection.